AMYOTROPHIC LATERAL SCLEROSIS AND EFFECTS OF VIBRATIONS - Veselinka Nestorova; Borislav Ivanov; Ivan Dimitrov; Kalina Drenska; Ara Kaprelyan (Peytchinski Publishing, 2018)
Amyotrophic lateral sclerosis (ALS) is a severe and fatal neurodegenerative disorder affecting both the upper and lower motor neurons. We present the clinical cases of four patients with ALS and vibration syndrome. All patients had over 20 years of exposure to general and local vibrations and common subjective complaints: pain, paresthesia, twitching and weakness of limb muscles. Evidence of ALS syndrome was demonstrated by the abnormal neurological examination (pseudobulbar syndrome and pyramidal signs) as well as by neurophysiological studies (peripheral motor neuron degeneration). We discuss the possible relationship between the exposure to general and local vibrations and the ALS syndrome in our patients, and the role of vibrations as a possible risk factor for the disease. Occupational contact with chemicals and pesticides is also discussed as a risk factor.